A microscopy-compatible temperature regulation system for single-cell phenotype analysis – demonstrated by thermoresponse mapping of microalgae. Issue 9 (7th April 2021) - Andersson, Martin; Johansson, Sofia; Bergman, Henrik; Xiao, Linhong; Behrendt, Lars; Tenje, Maria
Abstract : A heat-stage for spatiotemporal temperature control in microfluidic chips is developed. The technology is used for mapping thermoresponses of single cells of Symbiodinium in order to improve our understanding of temperature-induced coral bleaching. Abstract : This work describes a programmable heat-stage compatible with in situ microscopy for the accurate provision of spatiotemporally defined temperatures to different microfluidic devices. The heat-stage comprises an array of integrated thin-film Joule heaters and resistance temperature detectors (RTDs). External programming of the heat-stage is provided by a custom software program connected to temperature controllers and heater–sensor pairs. Biologically relevant (20–40 °C) temperature profiles can be supplied to cells within microfluidic devices as spatial gradients (0.5–1.5 °C mm −1 ) or in a time-varying approach via e.g. step-wise or sinusoidally varying profiles with negligible temperature over-shoot. Demonstration of the device is achieved by exposing two strains of the coral symbiont Symbiodinium to different temperature profiles while monitoring their single-cell photophysiology via chlorophyll fluorometry. This revealed that photophysiological responses to temperature depended on the exposure duration, exposure magnitude and strain background. Moreover, thermal dose analysis suggested that cell acclimatisation occurs under longer temperature (6 h) exposures but not under shorter temperature exposures (15 min). As the thermal sensitivity of Symbiodinium mediates the thermal tolerance in corals, our versatile technology now provides unique possibilities to research this interdependency at single cell resolution. Our results also show the potential of this heat-stage for further applications in fields such as biotechnology and ecotoxicology.